Fostering Intercultural Communicative Competence in English Language Teaching at International Schools - Nurul Fitriani; Riska Awaliyah (Balla' Caradde Education, 2026)
As intercultural communication becomes increasingly essential in global education, effective integration of Intercultural Communicative Competence (ICC) in English Language Teaching (ELT) remains insufficiently understood, particularly in international school contexts. This qualitative case study investigated how an English teacher at Al Azhar Yogyakarta World School integrated ICC into classroom practices and the challenges encountered. Data were collected through classroom observations and semi-structured interviews. The findings reveal that ICC was fostered through inclusive learning environments, culturally relevant materials, and project-based learning (PBL). However, teachers faced persistent challenges in balancing curriculum requirements with intercultural objectives, addressing culturally sensitive issues, accommodating diverse student backgrounds, and accessing appropriate instructional resources. This study highlights the urgent need for sustained professional development and institutional support to strengthen teachers’ intercultural pedagogical competence. By providing context-specific evidence from an international school in Indonesia, the study contributes practical insights for advancing ICC integration in ELT.